The Importance of Cognition in Education - Felicia, Ceausu (International Journal of Publication and Social Studies, 2019)
Cognitive or mental architectures are models made up of input - output type modules of the central nervous system activity, formed with the help of white, black or grey cybernetic “boxed” and of the determination connection. Despite the great existing differences between the biochemical and electronic processing of information, the mental architectures aid in comparing the human intelligence with the artificial one and even contribute to the creation of a common language between the human and the animal intelligence (taking into account static and dynamic representations). Based on that cultural and social representations share a „situational“semiotics, we use a common language with connection to referentiality or not, for physical or social representations. In this work I will create the formal model as a representation more or less simplified of a “material world”. We will, therefore, admit the presence of some physical-mathematical, psychic and semiotic models (depending on the language). The physical - mathematical models refer to the image of the world starting from the 4th dimensional continuum perceived by our senses. The models are referential rather than imaginary because physics inhibits the mathematical tendency of generating too many possible worlds. On the contrary, the psychological models can be also reported to imaginary luxurious worlds due to the outcome of our imagination which can be hardly quelled.